Does the Effect of Exposure to TV Sex on Adolescent Sexual Behavior Vary by Genre?. (February 2013) - Gottfried, Jeffrey A.; Vaala, Sarah E.; Bleakley, Amy; Hennessy, Michael; Jordan, Amy
Using the Integrated Model of Behavioral Prediction, this study examines the effects of exposure to sexual content on television by genre, specifically looking at comedy, drama, cartoon, and reality programs, on adolescents' sex-related cognitions and behaviors. Additionally, we compared the amount and explicitness of sexual content as well as the frequency of risk and responsibility messages in these four genres. Findings show that overall exposure to sexual content on television was not related to teens' engagement in sexual intercourse the following year. When examined by genre, exposure to sexual content in comedies was positively associated while exposure to sexual content in dramas was negatively associated with attitudes regarding sex, perceived normative pressure, and ultimately engaging in sex 1 year later. Implications of adolescent exposure to various types of content and for using genre categories to examine exposure and effects are discussed.